Richard Smith Van Dyke papers - Van Dyke, Richard Smith, 1840-1864.; Battey, George Magruder, 1887-1965.
Typewritten transcript of captions in Van Dyke's photograph album entitled, "The Princeton Civil War Class of 1861," together with a biographical sketch of him written by his nephew, George Magruder Battey, and photograph of Van Dyke.
In part, typewritten transcripts.
Confederate soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Princeton University -- History -- 19th century; Princeton University -- Students; United States -- History -- Civil War, 1861-1865.; Soldiers -- Confederate States of America